GANGGUAN SPEKTRUM BIPOLAR PADA MAHASISWA DI UNIVERSITAS AIRLANGGA (STUDI KOMPARATIF PREVALENSI DAN FAKTOR RISIKO) - Marwati, Indah Shofie; Djuari, Lilik; Karimah, Azimatul (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
Bipolar Spectrum Disorder is relatively common and often occurs since college years. This study analyzed the differences between prevalence and risk factors of Bipolar Spectrum Disorder in medical and non medical students at Universitas Airlangga, Surabaya. It was an observational analytic study design with a cross-sectional approach using accidental sampling technique. The population and subject were medical students and accounting students batch 2017. Data collection was carried out in 2 ways, by face to face questionnaire filling and by electronic questionnaire (google form). Total respondents recruited were 441 students. The prevalence of medical students who received positive screening results for Bipolar Spectrum Disorder was 19 (7.8%) for medical students and 9 (4.5%) for non medical students. There is no significant difference between the prevalence and risk factors of Bipolar Spectrum Disorder in medical and non-medical students. However, study found significant difference in relations of risk factors such as history of maternal complication, physically abused in childhood, experienced severe failure, sibling committed suicide, experiencing the stress of life, experiencing catastrophic event, history of severe physical illness with positive Bipolar Spectrum Disorder among students.